Thermo-dynamic irreversibility induced by natural convection in square enclosure with inner cylinder. Part-I: Effect of tilted angle of enclosure. (June 2016) - Mun, Gi Su; Doo, Jeong Hoon; Ha, Man Yeong
Highlight: The immersed boundary method was used, based on the finite volume method. Abstract: Two-dimensional numerical simulations were conducted to investigate the natural convection heat transfer induced by the temperature difference between cold walls of the tilted square enclosure and a hot inner circular cylinder for different Prandtl numbers (10 −2 ⩽ Pr ⩽ 10 2 ) and Rayleigh numbers (10 3 ⩽ Ra ⩽ 10 6 ). The numerical solutions are obtained using an accurate and efficient immersed boundary method. The outer square enclosure is tilted from γ = 0° to γ = 45° by each 5°. Detailed analysis results including the distribution of streamlines, isotherms and Nusselt numbers are presented. The entropy generation and corresponding Bejan number in the enclosure are analyzed to estimate the thermo-dynamic irreversibility accompanied by the natural convection in the system.